1993
DOI: 10.1161/01.atv.13.5.640
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a nonhypotensive long-term infusion of ANP on the mechanical and structural properties of the arterial wall in Wistar-Kyoto and spontaneously hypertensive rats.

Abstract: A nonhypotensive dose of atrial natriuretic peptide (ANP) was infused (60 pg/kg body wt per day s.c. by osmotic pump) for 25 days in 16-week-old normotensive Wistar-Kyoto rats (WKYs, TI = 12) and age-matched spontaneously hypertensive rats (SHRs, n = 12). During the infusion period, systolic blood pressure, urinary volume, and cyclic guanosine monophosphate (cGMP) excretion/12 hr were measured once a week in both groups. Then mechanical and morphological properties of the arterial wall and plasma ANP levels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 49 publications
0
2
1
Order By: Relevance
“…Several reports have demonstrated a lack of increased collagen in hypertension (Bezie et al, 1998a ; Koffi et al, 1998 , 1999 ; van Gorp et al, 2000 ; Sehgel et al, 2015 ), with some reporting decreases in vascular collagen (Cox, 1981 ; Mizutani et al, 1999 ). These stand in contrast to studies of hypertension that report observations of increased vascular collagen (Mourlon-Le Grand et al, 1993 ; Koffi et al, 1998 , 1999 ), in a similar fashion as reported in studies of aging. A time-course study by Hu and colleagues found aortic collagen increased initially following induction of hypertension, but the concentration returned to levels not different from the sham control in the long-term (Hu et al, 2008 ).…”
Section: Major Mechanisms Mediating Causes Of Increased Vascular Stifcontrasting
confidence: 46%
“…Several reports have demonstrated a lack of increased collagen in hypertension (Bezie et al, 1998a ; Koffi et al, 1998 , 1999 ; van Gorp et al, 2000 ; Sehgel et al, 2015 ), with some reporting decreases in vascular collagen (Cox, 1981 ; Mizutani et al, 1999 ). These stand in contrast to studies of hypertension that report observations of increased vascular collagen (Mourlon-Le Grand et al, 1993 ; Koffi et al, 1998 , 1999 ), in a similar fashion as reported in studies of aging. A time-course study by Hu and colleagues found aortic collagen increased initially following induction of hypertension, but the concentration returned to levels not different from the sham control in the long-term (Hu et al, 2008 ).…”
Section: Major Mechanisms Mediating Causes Of Increased Vascular Stifcontrasting
confidence: 46%
“…Similar observations and findings have been made in the abdominal aorta 12,23 , mesenteric 16,24 and cerebral 24 arteries. However, it is noted that in other studies of the SHR, contradictory results have been reported for the thoracic aorta 13,14,25 and mesenteric artery 26 . In fact, of the numerous studies surveyed on the effect of hypertension, per se, on vascular collagen, inconsistency seems to be the common feature of the collective studies.…”
Section: Discussionmentioning
confidence: 83%
“…Studies of the effect of natriuretic peptides on collagen deposition in cardiovascular tissue in vivo are few but supportive of an inhibitory action. Thus, Mourlon‐le‐Grand et al (1992) found that continuous infusion of ANP reduced collagen deposition in the arterial wall of spontaneously hypertensive rats. Monopoli et al (1992) have reported that chronic administration of a neutral endopeptidase inhibitor (which inhibits natriuretic peptide degradation) inhibited collagen deposition in the hypertrophied ventricle of these animals.…”
Section: Discussionmentioning
confidence: 91%